Implementing Efficient Market Structure - Veronika Grimm; Frank Riedel; Elmar G. Wolfstetter (Center for Economic Studies and ifo Institute (CESifo), 2000)
This article studies the design of optimal mechanisms to regulate entry in natural oligopoly markets, assuming the regulator is unable to control the behavior of firms once they are in the market. We adapt the Clark-Groves mechanism, characterize the optimal mechanism that maximizes the weighted sum of expected social surplus and expected tax revenue, and show that these mechanisms generally avoid budget deficits and prevent excessive entry.
Keywords: 330; Mechanism design; natural oligopoly; auctions; entry